Combination of the fungus Beauveria bassiana and pheromone in an attract‐and‐kill strategy against the banana weevil, Cosmopolites sordidus. Issue 1 (April 2014) - Lopes, Rogério B.; Laumann, Raul A.; Moore, Dave; Oliveira, Márcio W. M.; Faria, Marcos
Abstract An attract‐and‐kill approach based on pellets from soybean or palm stearin fats blended with the entomopathogenic fungus Beauveria bassiana (Bals.) Vuill. sensu lato and the aggregation pheromone sordidin (Cosmolure®) was tested against the banana weevil, Cosmopolites sordidus (Germar) (Coleoptera: Curculionidae). The viability of B. bassiana conidia, blended with hydrogenated oil and exposed for up to 150 min to heating at 50 °C, was not affected and the aggregation pheromone did not undergo any decomposition. Conidial viability in pellets decreased by 50% after an average of 15.1 and 9.1 days at 25 and 40 °C, respectively, when packaged in polypropylene bags. Active packaging (hermetic bag + O2/moisture‐absorbing sachet) increased the shelf lives almost 10 and 6 times at 25 and 40 °C, respectively. In olfactometer bioassays, fat pellets amended with pheromone (sordidin, 1% wt/vol) were highly attractive to C. sordidus adults for up to 15 days, after which the pheromone release rate had decreased by about 90% and pellets were no longer attractive. Pellets with pheromone and conidia were as attractive to C. sordidus as banana rhizomes, and considerably more attractive than pieces of pseudostem. In no‐choice experiments conducted in boxes, survival of insects exposed to fungus‐impregnated pellets was affected by fat type (soybean fat vs. palm stearin) and bioassay temperature (25 vs. 30 °C), with results favoring soybean fat pellets at the higher temperature (96.9% of mortality after 18 days and ST50 of 7.7 days). However, mortality levels were low (21.7% for soybean fat pellets) or very low (1–5% for palm stearin pellets) in choice experiments carried out at 25 °C when fungus‐impregnated pellets were applied before or after exposure of pseudostem residues to insects, respectively. The potential of this delivery system to manage C. sordidus populations and other insect pests (including those with cryptic habits) is discussed.